(untitled) (International Journal of Studies in Nursing, 2024)
It is imperative that pediatric health care providers preach and practice the importance of a thorough newborn (NB) assessment, whether within the first 24 hours of life, during the very first outpatient NB examination, or at any outpatient visits with the provider. These NB assessments identify abnormalities associated with anomalies, birth injuries, jaundice, or cardiopulmonary issues. The American Academy of Pediatrics (AAP, 2024) recommends that Preventative Pediatric Health Care include NBs being seen for their initial or interval history between days three to five of life.